Understanding spirituality: a synoptic view. Issue 4 (30th July 2012) - Cobb, Mark; Dowrick, Christopher; Lloyd-Williams, Mari
Abstract : Background: Spirituality is an important component of palliative care that is incorporated into practice and the subject of research. A literature review by the authors indicated that many studies into the spiritual needs of palliative care patients operationalised highly reductive constructs of spirituality and relied upon unexamined assumptions and concepts. Methods: We examine the use of models as a strategy to explain how spirituality functions in the lives of patients and critically review examples of descriptive modelling and mathematical modelling. The explanatory and predictive potential of these techniques is considered along with methodological limitations in representing complex aspects of human nature in models. Proposal: We propose a realistic synoptic model to explain how spirituality is lived and experienced in the wider context of a mental, personal and social world. We describe the essential conceptual apparatus and mechanisms of lived spirituality including beliefs, behaviour and experience, and we suggest that spirituality is a feature and capacity of the system as a whole. Conclusions: The synoptic model provides an explanation of how spirituality operates in the totality of patients' lives and aims to capture aspects of spirituality that remain neglected by researchers and practitioners. It is proposed as a corrective to reductionist approaches and supports the contribution of different disciplines and different ways of thinking about spirituality.